Caribbean Bulimulus revisited: physical moves and molecular traces (Mollusca, Gastropoda, Bulimulidae) - Breure,Abraham S.H. (PeerJ, 2016)
Twenty-five samples of Bulimulus species are studied, partly from localities within their known distribution range, partly based on interceptions where the material originates from localities where the species seem to be recently introduced and non-native. Molecular study of cytochrome oxidase 1 (CO1) reveals the origin of some of these introductions, but is less conclusive for others. Four different methods for species delimitation were applied, which did not result in unambiguous species hypotheses. For a rapid identification of morphologically indistinct species, a more comprehensive database of sequences is needed.
Keywords: Orthalicoidea; Distribution; Central America; Ecuador; West Indies; Florida; Alien species; Phylogenetics